Presence of a predator image in potential breeding sites and oviposition responses of a dengue vector - Hamady, Dieng; Nur Farrahana, Suradi; Hafijah, Hakim; Fatimah, Abang; Nur Ezzati, Aliasan; Fumio, Miake; Wan Fatma, Zuharah; Nur Faeza, A. Kassim; Abdul Hafiz, Ab Majid; Nik, Fadzly; Ronald E., Morales Vargas; Noppawan P., Morales; et al. (Elsevier, 2017)
In dengue vector control, attempts to minimize or replace the use of pesticides have mostly involved use of predators, but success has been severely impeded by difficulties associated with financial and environmental costs, predator mass production, and persistence in target habitats. Visual deterrents have been used successfully to control animal pests, in some cases in an effort to replace pesticide use. Despite evidence that visual signals are crucial in site choice for egg deposition by dengue vectors, and that female mosquitoes respond to artificial predation, the role of predator intimidation as it affects the oviposition behavior of dengue vectors remains largely unexplored. Here, we examined the oviposition responses of Aedes aegypti exposed to various mosquito predator pictures. Gravid females were presented with equal opportunities to oviposit in two cups with predator images [Toxorhynchites splendens—TXI, Goldfish (Carassius auratus)—small (SFI) and large (LFI) and Tx. splendens + Goldfish—TXFI] and two others without pictures. Differences in egg deposition were examined between sites with and without these images. When given a chance to oviposit in cups with and without TXI, Ae. aegypti females were similarly attracted to both sites. When provided an opportunity to oviposit in cups displaying pictures of fish (SFI or LFI) and blank cups, egg deposition rates were much lower in the fish picture sites. Females showed a preference for blank cups over TXFI for egg deposition. They also equally avoided cups with pictures of fish, regardless of the size of the picture. Our results indicate that the presence of images of goldfish and their association with Tx. larvae significantly reduced egg deposition by Ae. aegypti, and this was not the case with the predatory larvae alone. The observations that the images of natural predators can repel gravid females of a dengue vector provide novel possibilities to develop effective and inexpensive alternative tools to harmful insecticides.